2018
DOI: 10.1016/j.isci.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Anti-digestive Hydrogels Selected by a Simulated Gut Microfluidic Chip for Closing Gastrointestinal Fistula

Abstract: SummaryThe anti-digestive features given to hydrogels can prolong their action time in gut environment; however, these types of hydrogels have rarely been reported. Inspired by indigestibility of dietary fibers, we introduced an injectable covalent hydrogel through photopolymerization of glycidyl methacrylate-modified xanthan. This newly synthesized hydrogel exhibited a specific concentration-dependent porosity, swelling ratio, and stiffness. The intestinal epithelial cells-6 could grow on the surface of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…First, natural and synthetic hydrogel scaffolds are potential alternatives to Matrigel, since they exhibit a 3D network structure similar to the environment of stem cell niches (Kratochvil et al, ). Most of these scaffolds have definite composition and clear description of their biocompatibilities (Brown & Anseth, ; Huang, Li, et al, ). They can control the development of intestinal organoids by creating different biophysical signals.…”
Section: Introductionmentioning
confidence: 99%
“…First, natural and synthetic hydrogel scaffolds are potential alternatives to Matrigel, since they exhibit a 3D network structure similar to the environment of stem cell niches (Kratochvil et al, ). Most of these scaffolds have definite composition and clear description of their biocompatibilities (Brown & Anseth, ; Huang, Li, et al, ). They can control the development of intestinal organoids by creating different biophysical signals.…”
Section: Introductionmentioning
confidence: 99%
“…What we introduce in this case report is a hollow and curving pipe stent with integrated wall, which is a combination of isolation technique with 3D printing[11], and can be applied to plug EAF at the very early stage of OA. Unlike silicone fistula plug reported by Ozer et al[5] or PEG tube reported by Miranda et al[7], 3D-printed “fistula stent” can be used to block EAF as soon as the EAF is discovered or formed.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 As for the stiffness, adequate strength is important for successful anastomosis; otherwise, the scaffolds would be ruptured and lead to leakage. Another role of stiffness is to regulate cell proliferation, differentiation, and functionalization 29 , 43 but the value in the achievement of the optimal status of intestinal cells needs to be precisely determined. In addition, Costello et al 44 created scaffold topography in the shape of intestinal villi, which enabled cell differentiation along the villous axis.…”
Section: Techniques Of Gut Bioengineeringmentioning
confidence: 99%